Tissue Engineering the Annulus Fibrosus Using 3D Rings of Electrospun PCL:PLLA Angle-Ply Nanofiber Sheets - Shamsah, Alyah H.; Cartmell, Sarah H.; Richardson, Stephen M.; Bosworth, Lucy A. (Frontiers in Bioengineering and Biotechnology, 2020)
Treatments to alleviate chronic lower back pain, caused by intervertebral disc herniation as a consequence of degenerate annulus fibrosus (AF) tissue, fail to provide long-term relief and do not restore tissue structure or function. The future of AF tissue engineering relies on the production of its complex structure assisted by the many cells that are resident in the tissue. As such, this study aims to mimic the architecture and mechanical environment of outer AF tissue using electrospun fiber scaffolds made from a synthetic biopolymer blend of poly(ε-caprolactone) (PCL) and poly(L-lactic) acid (PLLA). Initially, an aligned bilayer PCL:PLLA scaffold was manually assembled at ±30o fibers direction to resemble the native AF lamellar layers; and bovine AF cells were used to investigate the effect of construct architecture on cell alignment and orientation. Bilayer scaffolds supported cell adhesion and influenced their orientation. Furthermore, significant improvements in tensile stiffness and strength were achieved, which were within the reported range for human AF tissue. Electrospun bilayer scaffolds are, however, essentially two-dimensional and fabrication of a complete three-dimensional (3D) circular construct to better replicate the AF's anatomical structure is yet to be achieved. For the first time, a custom-built Cell Sheet Rolling System (CSRS) was utilized to create a 3D circular lamellae construct that mimics the complex AF tissue and which overcomes this translational limitation. The CSRS equipment is a quick, automated process that allows the creation of multilayered, tube-like structures (with or without cells), which is ideal for mimicking human cervical AF tissue in term of tissue architecture and geometry. Tube-like structures (6 layers) were successfully created by rolling ±30° bilayer PCL:PLLA scaffolds seeded with bovine AF cells and subsequently cultured for three weeks. Cells remained viable, purposefully oriented with evidence of collagen type I deposition, which is the main structural component of AF tissue. This is the first study focused on applying CSRS technology for the fabrication of a more clinically-relevant, 3D tissue engineered scaffold for AF tissue regeneration.